Real-World Experience Treating Pediatric Epilepsy Patients With Cenobamate - Makridis, Konstantin L.; Bast, Thomas; Prager, Christine; Kovacevic-Preradovic, Tatjana; Bittigau, Petra; Mayer, Thomas; Breuer, Eva; Kaindl, Angela M. (Frontiers in Neurology, 2022)
Introduction In one third of all patients with epilepsy, seizure freedom is not achieved through anti-seizure medication (ASM). These patients have an increased risk of earlier death, poorer cognitive development, and reduced quality of life. Cenobamate (CNB) has recently been approved as a promising novel ASM drug for the treatment of adults with focal-onset epilepsy. However, there is little experience for its application in pediatric patients. Methods In a multicenter study we evaluated retrospectively the outcome of 16 pediatric patients treated “off label” with CNB. Results In 16 patients with a mean age of 15.38 years, CNB was started at an age of 15.05 years due to DRE. Prior to initiation of therapy, an average of 10.56 (range 3–20) ASM were prescribed. At initiation, patients were taking 2.63 (range 1–4) ASM. CNB was increased by 0.47 ± 0.27mg/kg/d every 2 weeks with a mean maximum dosage of 3.1 mg/kg/d (range 0.89–7) and total daily dose of 182.81 mg (range 50–400 mg). Seizure freedom was achieved in 31.3% and a significant seizure reduction of >50% in 37.5%. Adverse events occurred in 10 patients with fatigue/somnolence as the most common. CNB is taken with high adherence in all but three patients with a median follow-up of 168.5 days Conclusion Cenobamate is an effective ASM for pediatric patients suffering from drug-resistant epilepsy. In addition to excellent seizure reduction or freedom, it is well-tolerated. Cenobamate should be considered as a novel treatment for DRE in pediatric patients.